DAAM2 is elevated in the circulation and placenta in pregnancies complicated by fetal growth restriction and is regulated by hypoxia - Natasha de Alwis (Nature Portfolio, 2021)
Abstract Previously, we identified increased maternal circulating DAAM2 mRNA in pregnancies complicated by preterm fetal growth restriction (FGR). Here, we assessed whether circulating DAAM2 mRNA could detect FGR, and whether the DAAM2 gene, known to play roles in the Wnt signalling pathway is expressed in human placenta and associated with dysfunction and FGR. We performed linear regression analysis to calculate area under the ROC curve (AUC) for DAAM2 mRNA expression in the maternal circulation of pregnancies complicated by preterm FGR. DAAM2 mRNA expression was assessed across gestation by qPCR. DAAM2 protein and mRNA expression was assessed in preterm FGR placenta using western blot and qPCR. DAAM2 expression was assessed in term cytotrophoblasts and placental explant tissue cultured under hypoxic and normoxic conditions by qPCR. Small interfering RNAs were used to silence DAAM2 in term primary cytotrophoblasts. Expression of growth, apoptosis and oxidative stress genes were assessed by qPCR. Circulating DAAM2 mRNA was elevated in pregnancies complicated by preterm FGR [p < 0.0001, AUC = 0.83 (0.78–0.89)]. Placental DAAM2 mRNA was detectable across gestation, with highest expression at term. DAAM2 protein was increased in preterm FGR placentas but demonstrated no change in mRNA expression. DAAM2 mRNA expression was increased in cytotrophoblasts and placental explants under hypoxia. Silencing DAAM2 under hypoxia decreased expression of pro-survival gene, BCL2 and oxidative stress marker, NOX4, whilst increasing expression of antioxidant enzyme, HMOX-1. The increased DAAM2 associated with FGR and hypoxia implicates a potential role in placental dysfunction. Decreasing DAAM2 may have cytoprotective effects, but further research is required to elucidate its role in healthy and dysfunctional placentas.